Sobre las dificultades de aprendizaje de los verbos copulativo ser y estar. Un estudio de campo con aprendientes islandeses y una propuesta - Lobillo Sabate, Celia Marina, 1987- (2013)
The purpose to which this project has been aiming is to discover, through students of spanish as a foreign language in Iceland, the difficulties that appear in the learning of the copulative verbs ser-estar. To that extent, various works and articles related to the topic and previously published have been analyzed and a field study has been conducted among both the teacher and student corpus in order to gather information regarding the teaching of this language in secondary education structures and universities. Through the results, that have been analyzed and exploited, a didactic suggestion has been reached, which is divided into a grammatical explanation aiming at avoiding the mistake and a didactic suggestion of correction with the goal of adapting itself in the best way possible to the needs of the students of spanish as a foreign language in Iceland.